A multi-perspective exploration of the environmental website disclosure in global manufacturing - Heiko Thimm; Karsten Boye Rasmussen (Business Strategy and the Environment, 2022)
In this work, more than 340 of the largest manufacturing companies from China, Europe, Japan, and the United States are analysed to measure the extent of their environmental website disclosure from multiple perspectives, to explore determining factors of disclosure and to investigate whether disclosure correlates to scores of environmental performance ratings. The study data set included more than 80 website observation items, data about downloadable annual sustainability reports, financial performance data and the environmental scores in the CDP Rating and the Refinitiv ESG Scores. Descriptive statistical analyses and correlation analyses were performed for the entire sample and for the regional subsets of the sample. One of the major results is that all regions show low levels of website disclosure. However, some variation in the extent of disclosure was found. The lowest level of disclosure was found for Chinese websites. Higher levels were observed for the companies from Europe, Japan and the United States. The analysis of the reports revealed that only one-third of the sample companies from China but more than half of the companies from Europe, Japan and the United States supply recent reports. It was also found that integrated reports are less used in the United States, particularly when compared with companies from Europe and Japan. Insights also suggest that there is a weak to moderate correlation between one of the disclosure scores used and the Refinitiv ESG Scores. Further correlation analyses did not provide indications that company age and financial performance are to be considered determining factors of environmental website disclosure.
Keywords: 330; corporate environmental management; environmental reporting; environmental scores; environmental sustainability; environmental website disclosure; ESG rating; explorative research study; global production industry; sustainability disclosure; sustainability reporting